2015
DOI: 10.18565/cardio.2015.10.96-108
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Aspects in Cardiac Rehabilitation: From Theory to Practice. A Position Paper From the Cardiac Rehabilitation Section of The European Association of Cardiovascular Prevention and Rehabilitation of the European Society of Cardiology

Abstract: A large body of empirical research shows that psychosocial risk factors (PSRFs) such as low socio-economic status, social isolation, stress, Type-D personality, depression and anxiety increase the risk of incident coronary heart disease (CHD) and also contribute to poorer health-related quality of life (HRQL) and prognosis in patients with established CHD.PSRFs may also act as barriers to lifestyle changes and treatment adherence and may moderate the effects of cardiac rehabilitation (CR). Furthermore, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
2
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 38 publications
1
106
2
18
Order By: Relevance
“…99,100 Clinical depression and depressive symptoms predict incident CAD (RR 1.6 and 1.9, respectively) 101 and worsen its prognosis (RR 1.6 and 2.4, respectively). 92,96,101,102 Vital exhaustion, most likely representing somatic symptoms of depression, significantly contributed to incident CAD (population attributable risk 21.1% in women and 27.7% in men). The NRI improved significantly.…”
Section: B 72 73mentioning
confidence: 99%
See 1 more Smart Citation
“…99,100 Clinical depression and depressive symptoms predict incident CAD (RR 1.6 and 1.9, respectively) 101 and worsen its prognosis (RR 1.6 and 2.4, respectively). 92,96,101,102 Vital exhaustion, most likely representing somatic symptoms of depression, significantly contributed to incident CAD (population attributable risk 21.1% in women and 27.7% in men). The NRI improved significantly.…”
Section: B 72 73mentioning
confidence: 99%
“…103 Panic attacks also increase the risk of incident CAD (RR 4.2). 104 Anxiety is an independent risk factor for incident CAD (RR 1.3), 92 for cardiac mortality following AMI [odds ratio (OR) 1.2] 105 and cardiac events (OR 1.7). 106 Meta-analyses reported a 1.5-fold risk of CVD incidence, a 1.2-fold risk of CAD and 1.7-fold risk for stroke in patients with schizophrenia, 107 and a 1.3-fold risk for incident CAD, even after adjustment for depression, in patients with posttraumatic stress disorder.…”
Section: B 72 73mentioning
confidence: 99%
“…Psychological factors have been identified as an important predictor for program adherence (Alavi et al, ; Sarrafzadegan et al, ). Patients with CVD often experience stress (Dimsdale, ), which not only has a negative effect on their health and well‐being (Brummett et al, ) but also acts as a barrier to lifestyle change (Pogosova et al, ). Percieved stress could inhibit adherence to prescribed treatment interventions in CVD patients (Qi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In assessing the lifestyle before hospitalization, the highest degree of agreement occured with the statements "I was often tense, angry or worried about the events in society" and "I was often tense, angry or worried while following the media". These findings can be seen in the context of numerous studies in which psychosocial risk factors for cardiovascular disease development have shown that people who tend to experience negative affective states and poor mood are generally prone to develop cardiovascular disease (8,9,11,12). Negative emotions act as stressors.…”
Section: Discussionmentioning
confidence: 69%